Administrative procedures and political control of the bureaucracy - Balla, Steven J. (1998)
Positive theorists have argued that administrative procedures enhance political control of the bureaucracy, in part by predisposing agencies toward policy choices preferred by legislators' favored constituents. Although this "deck-stacking" argument has been both influential and controversial, few scholars have subjected it to empirical examination. This article assesses the operation of a prominent administrative procedure - the notice and comment process - in the context of Medicare physician payment reform, a fundamental restructuring of the way in which the Medicare program pays for physician services. I find, contrary to the deck-stacking thesis, that the Health Care Financing Administration (HCFA) was more responsive to physicians expecting reductions in fees than to the intended beneficiaries of the new payment system. Although these results do not necessarily imply that Congress exerted little influence over HCFA decision making, they suggest that certain administrative procedures do not operate as instruments of political control. - Reproduced
Keywords: Bureaucracy